2011
DOI: 10.1016/s1995-7645(11)60156-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and population dynamics of sand flies in a new focus of visceral leishmaniasis in Eastern Azarbaijan Province, North western of Iran

Abstract: This study is the first detailed research in terms of species composition, density, accumulated degree-day and diversity of sand flies in an endemic focus of visceral leishamaniasis in Azarshahr district. The population dynamics of sand flies in Azarshahr district were greatly affected by climatic factors. According to this study the highest activity of the collected sand fly species occurs at the teritary week of August. It could help health authorities to predicate period of maximum risk of visceral leishama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several studies in some restricted regions of Azarbayjan‐e‐sharqi and Ardabil provinces, two endemic foci of visceral leishmaniasis, have been carried out in order to identify the sand fly fauna and probable Leishmania infection. Hazratian et al (2011) studied the phenology and population dynamics of sand flies in Azar shahr district. To our knowledge, no investigation has been carried out to study and quantify the possible effects of altitude and physical barriers on sand fly populations in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in some restricted regions of Azarbayjan‐e‐sharqi and Ardabil provinces, two endemic foci of visceral leishmaniasis, have been carried out in order to identify the sand fly fauna and probable Leishmania infection. Hazratian et al (2011) studied the phenology and population dynamics of sand flies in Azar shahr district. To our knowledge, no investigation has been carried out to study and quantify the possible effects of altitude and physical barriers on sand fly populations in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been admitted that phlebotomine sand flies have a more or less definite seasonal distribution pattern in Mediterranean countries, become visible in late spring or early summer, and are active until early autumn ( 53 , 54 ). However, various studies have verified the bimodal pattern of temporal dispersion of phlebotomine sand flies with one peak in spring and another in summer or autumn ( 11 , 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is little data about the biodiversity of Iranian sand flies, indices for other species of insects were studied in northern Iran [ 54 , 55 ]. Findings of this study showed higher biodiversity (Mean: H ‘=1.21, J’ = 0.29) in the area compared to the northeast (H’ = 0.527–1.033, J’ = 0.345–0.380) (18) and northwest (H’ = 0.4131, J’ = 0.5309) [ 42 ] as well as lower in East Azerbaijan Province (H’ = 1.413–1.918) [ 23 ], and the Provinces of East and West Azerbaijan and Ardabil (H’ = 1.68–2.30, J’ = 0.73–0.88) [ 38 ]. Decreased species diversity in urban and semi-urban areas compared to natural (Khorasha) can also be due to the increase in population of dominant species such as Ph.…”
Section: Discussionmentioning
confidence: 99%
“…There are plenty of indices to study for biodiversity, but the most common are Simpson and Shannon-Wienner [ 20 ]. Biodiversity of Phlebotomine sand flies has been done in some provinces of Iran including Qom [ 21 ], Khuzestan [ 22 ] and West Azerbayjan Province [ 23 ].…”
Section: Introductionmentioning
confidence: 99%